PENGARUH TAYANGAN ADEGAN KEKERASAN YANG NYATA TERHADAP AGRESIVITAS - L Dion Praditya; Supra Wimbarti; Avin Fadilla Helmi (Faculty of Psychology, Universitas Gadjah Mada, 1999)
This research is intended to find the effects of real violence on aggressiveness. The hypothesis states that real violence shown on television will increase the aggressiveness of the viewer. The subjects of the research were 105 soldiers from the 403rd Infantry Battalion /WP. Experimental design were used as a method the pre-test post-test two-group. Data were obtained by an adaptation of the questionnaire made by Buss & Perry (1992), physiological measurement by measuring the systolic & diastolic blood pressure, observation, and interview. The result shows that real violence on television decreases the aggressiveness of the viewer, who is combat soldiers. The hypothesis is inconsistent with the study’s result because are in military background subjects are used in violence, unlike other researches that uses civilian subjects. Key Words: Real Violence, Aggressiviveness, Televison